2015
DOI: 10.1097/wnr.0000000000000465
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of autophagy in Hirschsprung’s disease

Abstract: Hirschsprung's disease (HD) is a common congenital gastrointestinal malformation, characterized by the lack of ganglion cells from the distal rectum to the proximal bowel, but the pathogenesis is not well understood. This paper evaluates the effects of autophagy in HD. Using electron microscopy, the autophagosomes were detected in three segments: narrow segment (NS), transitional segment (TS), and dilated segment (DS). Typical autophagosome structures are found in the Auerbach plexus of both NS and TS. Real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Autophagy may modulate the function of neural crest cells and contribute to the development of HSCR. Recent studies have con rmed the occurrence of autophagosome structures in the myenteric plexus of patients with HSCR who have narrow and transitional segments of intestine, and Beclin1 and LC3 expression was found to be highest in the narrow segment (10). Chen et al (11) has demonstrated the potential function of mir-939 in regulating LRSAM1 in HSCR, and suggests that autophagy may also contribute to the risk of HSCR.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy may modulate the function of neural crest cells and contribute to the development of HSCR. Recent studies have con rmed the occurrence of autophagosome structures in the myenteric plexus of patients with HSCR who have narrow and transitional segments of intestine, and Beclin1 and LC3 expression was found to be highest in the narrow segment (10). Chen et al (11) has demonstrated the potential function of mir-939 in regulating LRSAM1 in HSCR, and suggests that autophagy may also contribute to the risk of HSCR.…”
Section: Discussionmentioning
confidence: 99%